DEMANDA E POLÍTICAS PÚBLICAS PARA O ENSINO SUPERIOR NOS BRICS - Schwartzman, Simon (Caderno CRH, 2015)
Este artigo analisa a expansão do ensino superior nos países chamados BRICS. A aspiração crescente pelo ensino superior obriga os governos a gerir os custos de funcionamento desse sistema. As respostas de cada país variam com sua história, cultura e regime político. Todos eles enfrentam problemas semelhantes, como escassez de recursos e o poder político de atores do sistema de ensino superior e fora dele. Cinco dilemas se apresentam aos países: 1) expansão, igualdade de acesso e diversificação das matrículas, taxas de participação, o número e os tipos de instituições; 2) limitações financeiras; 3) regulação do ensino superior privado; 4) como fazer com que as instituições de ensino superior prestem mais contas a seus alunos, funcionários e à sociedade como um todo; e 5) qualidade e relevância social da aprendizagem e pesquisa em instituições de ensino superior. Utilizando dados e evidências das pesquisas mais recentes, o artigo mostra respostas comuns, com algumas exceções em cada caso: diversificação institucional; políticas de ação afirmativa; crescimento das matrículas nas ciências sociais, humanidades, profissões sociais e Educação; pouco sucesso nas políticas de internacionalização. Palavras-chave: Ensino Superior. BRICS. Igualdade de acesso. Financiamento ensino superior. Qualidade ensino superior. DEMAND AND PUBLIC POLICIES FOR HIGHER EDUCATION IN BRICS Simon Schwartzman This article analyzes the expansion of higher education in so-called BRICS countries. The growing aspiration for higher education obliges governments to manage the operational costs of this system. The answers from each country varied with its history, culture and political regime. They all faced similar problems as lack of resources and political power of actors in the higher education system and beyond. Five dilemmas appeared to all countries: (1) expansion, equal access and diversification of enrollment, participation rates, the number and types of institutions; (2) financial constraints; (3) regulation of the private higher education; (4) how to make higher education institutions to provide more accountable to their students, employees and society as a whole; and (5) quality and social relevance of learning and research in higher education institutions. Using data and evidence of the latest research, the article shows common responses, with some exceptions in each case. Institutional diversification; affirmative action; growth of enrollments in the social sciences, humanities, social professions and education; little success in internationalization policies. Keywords: Higher Education. BRICS. Equal access. Financing higher education. Quality of higher education. DEMANDE ET POLITIQUES PUBLIQUES POUR L’ENSEIGNEMENT SUPÉRIEUR AUX BRICS Simon Schwartzman Cet article analyse l’expansion de l’enseignement supérieur dans les pays dits BRICS. L’aspiration croissante de l’enseignement supérieur oblige les gouvernements à gérer les coûts de fonctionnement de ce système. Les réponses de chaque pays varient avec son histoire, la culture et le régime politique. Ils sont tous confrontés à des problèmes similaires tels que le manque de ressources et le pouvoir politique des acteurs du système de l’enseignement supérieur. Cinq dilemmes se présentent aux pays: (1) l’expansion, l’égalité d’accès et, les taux de participation, le nombre et les types d’institutions; (2) des contraintes financières; (3) la réglementation de l’enseignement supérieur privé; (4) la façon de rendre transparentes les institutions de l’enseignement supérieur; et (5) la qualité et la pertinence sociale de l’apprentissage et de la recherche dans les établissements d’enseignement supérieur. En utilisant les données des recherches les plus récentes, l’article montre des réponses communes, avec quelques exceptions dans chaque cas. Diversification institutionnelle; politiques de discrimination positive; la croissance des inscriptions dans les sciences humaines, les professions sociales et l’éducation; peu de succès dans les politiques d’internationalisation. Mots-clés: L’enseignement supérieur. BRICS. L’égalité d’accès. Le financement de l’enseignement supérieur. Qualité de l’enseignement supérieur. <small style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; background-color: #ffffff;">Publicação Online do Caderno CRH no Scielo: http://www.scielo.br/ccrh<span style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; float: none; display: inline ! important; background-color: #ffffff;"> <br style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; background-color: #ffffff;" /> <br style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; background-color: #ffffff;" /> <small style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; background-color: #ffffff;">Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br<span style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; float: none; display: inline ! important; background-color: #ffffff;">